Experimental Study on Thermal Elastohydrodynamic Lubrication Performance Calculation and Take-Off Speed of Thrust Bearing of Canned Motor Pump - Yanjun Cao; Yingjie Yu; Haiming Gang; Qichen Shang; Xiaozhe Meng; Mohan Yang; Qian Jia (Lubricants)
In this paper, the calculation model and method of the lubrication performance of the thrust bearing, which considers the thermal bomb deformation, are constructed based on the working characteristics of the main pump thrust of the nuclear power plant. The key design parameters of the tile package Angle θ are analyzed by taking the design parameters of the thrust-bearing tile as the variable. The circumferential fulcrum coefficient of tile, the influence of tile thickness B, and tile elastic modulus E on the lubrication performance of thrust bearing are analyzed to obtain improved design parameters. The lubrication performance of the thrust bearing includes the minimum oil film thickness hmin, the maximum temperature of oil film Tmax, total flow Qx, total power consumption W, maximum thermal deformation of axial bush δTmax, and the maximum elastic deformation of the axial bush δFmax. The scale test of the designed thrust bearing is carried out. The take-off speed of the bearing is tested and compared with the results of the theoretical analysis. The study results show that the influence is becoming more obvious from θo to hmin. Moreover, the impact becomes more obvious from Tmax to Qx, B to hmin, and Qx to δTmax and δFmax. Lastly, the impact is also obvious from E to Qx and δFmax.